Involvement in religion as a vital value: study of the religious population in Belarus - Karassyova, Svetlana G.; Shkurova, Elena V.; Shatrauski, Sergei I. (Journal of the Belarusian State University. Sociology, 2019)
The article presents the results of evaluating of the significance of religion in the life of the followers of different faiths in Belarus The significance of religion is one of the indicators of a multidimensional model of religiosity, used to study the multi-confessional environment. According to the study, Belarusian religious population, regardless of confessional affiliation, sufficiently appreciates the importance of religion in the life, but it captures not so much the existential, notional its function as an abstract-normative, social and regulatory.
Keywords: religiosity; multidimensional model of religiosity; religion; cross-confessional approach; degree of religiosity; value of religion